Linkage of whole genome sequencing with administrative health, and electronic medical record data for the study of autism spectrum disorder: Feasibility, Opportunities and Challenges. (2018) - Brooks, Jennifer; Anagnostou, Evdokia; Rahman, Farah; Tu, Karen; Uruthiramoorthy, Lavnaya; Nylen, Kirk; McLaughlin, John; Schull, Michael; Bronskill, Susan
No abstract available